Web Reasoning and Rule Systems Fourth International Conference, RR 2010, Bressanone/Brixen, Italy, September 22-24, 2010. Proceedings - Hitzler, Pascal; Lukasiewicz, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 4th International Conference on Web Reasoning and Rule Systems, RR 2010, held in Brixen-Bressanone, Italy, in September 2010. The 9 revised full papers, 6 revised short papers, and 4 poster papers presented together with 1 PhD paper, 2 system descriptions and 3 invited papers were carefully reviewed and selected from 41 submissions. The papers address all current topics in Web reasoning, Web-based knowledge, and rule systems such as representation techniques; rules and ontologies; reasoning languages; efficiency and benchmarking,; ontology languages; querying and optimization; reasoning with uncertainty, under inconsistency, and with constraints; rule languages and systems; rule interchange formats and markup languages; scalability; approximate reasoning; statistical methods and symbolic reasoning; as well as semantic Web services modeling and applications.
Invited Talks and Tutorial -- Query Answering under Non-guarded Rules in Datalog+/- -- Data Validation with OWL Integrity Constraints -- SPARQL1.1: New Features and Friends (OWL2, RIF) -- Full Papers -- Usability of a Visual Language for DL Concept Descriptions -- A Rule-Based Language for Complex Event Processing and Reasoning -- Analyzing the AIR Language: A Semantic Web (Production) Rule Language -- Query-Based Access Control for Ontologies -- On the Semantic Relationship between Datalog and Description Logics -- Inconsistency-Tolerant Semantics for Description Logics -- Extending Paraconsistent -- Redundancy Elimination on RDF Graphs in the Presence of Rules, Constraints, and Queries -- Defeasibility in Answer Set Programs via Argumentation Theories -- Short Papers -- A Rule-Based Approach to XML Processing and Web Reasoning -- Learning to Rank Individuals in Description Logics Using Kernel Perceptrons -- A Probabilistic Abduction Engine for Media Interpretation Based on Ontologies -- Secrecy-Preserving Query Answering for Instance Checking in -- Embeddings of Simple Modular Extended RDF -- KWilt: A Semantic Patchwork for Flexible Access to Heterogeneous Knowledge -- Poster/Position Papers -- Composition of Semantic Web Services in a Constructive Description Logic -- A Step toward Tight Integration of Fuzzy Ontological Reasoning with Forward Rules -- Rule-Based Spam E-mail Annotation -- A RESTful SWRL Rule Editor -- PhD Description -- On the Termination of the Chase Algorithm -- System Descriptions -- Processing RIF and OWL2RL within DLVHEX -- A RPL through RDF: Expressive Navigation in RDF Graphs.
Keywords: Computer science; Software engineering; Information systems; Data mining; Information storage and retrieval systems; Multimedia systems; Computer Science; Information Systems Applications (incl.Internet).; Information Systems and Communication Service; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Software Engineering; Multimedia Information Systems